Synthesis, characterization and thermal properties of polystyrene–poly(lactic acid)–polystyrene triblock copolymer via atom transfer radical polymerization. (August 2014) - Shen, Jun; Jiang, Wei; Liu, Ying; Wei, Rong-qing; Zhong, Yu; Li, Lin-ling; Xue, Gi; Liu, Xiao-ning
Polystyrene (PS)–poly(lactic acid) (PLA)–PS triblock copolymer is prepared with PLA and styrene (St) via atom transfer radical polymerization (ATRP). The structure and thermal properties of the copolymer are analyzed by infrared spectroscopy, gel permeation chromatography, nuclear magnetic resonance, thermogravimetry, differential scanning calorimetry and alcoholysis. The ATRP of St using bromine-terminated PLA as the initiator exhibits first-order kinetics and a low-molecular-weight distribution ( M w / M n  ≈ 1.5). The thermal stability of PLA is improved by copolymerization. Both the initial temperature of thermal decomposition and glass transition temperature are increased with an increasing length of PS block.